New-Onset Post-Operative Atrial Fibrillation in Patients Undergoing Coronary Artery Bypass Grafting Surgery - A Retrospective Case-Control Study - Cui,Xuehui (2022)
ABSTRACT Introduction: New-onset postoperative atrial fibrillation (POAF) is a common complication following coronary artery bypass grafting (CABG) surgery. Objective: To explore predictive factors and potential mechanisms of new-onset POAF in isolated off-pump CABG patients. Methods: Retrospective observational case-control study of 233 patients undergoing isolated off-pump CABG surgery between August 2018 and July 2020 at the Department of Thoracic and Cardiovascular Surgery, the Affiliated Drum Tower Hospital of Nanjing University Medical School. Associations between predictor variables and new-onset POAF were identified. The main outcome was new-onset POAF after CABG surgery. Results: A total of 75 (32.19%) patients developed new-onset POAF after CABG surgery. The new-onset POAF patients had advanced age, higher baseline systolic blood pressure, more preoperative use of diuretic drug, more transfusion of blood products, atrial dilation and postoperative positive inotropic drug treatment. Nineteen variates entered the multivariable logistic regression model with a Hosmer-Lemeshow test score of 7.565 (P=0.477). Postoperative left atrial enlargement, postoperative drainage in the first 24 hours and total length of hospital stay were statistically significant, while postoperative right atrial enlargement (OR and 95% CI, 7.797 [0.200, 304.294], P=0.272) and left atrial enlargement (3.524 [1.141, 10.886], P=0.029) assessed by echocardiography had the largest OR value. Conclusion: Atrial enlargement is strongly associated with new-onset POAF in patients with isolated off-pump CABG, thus it highlights the advantage of echocardiography as a useful tool for predicting new-onset POAF. Careful monitoring and timely intervention should be considered for these patients.